Peran Keimigrasian terhadap Penyalagunaan Izin Tinggal Warga Negara Asing di Kota Medan Pada Masa Pandemi Covid-19 - Rumagit, Joni; Isnaini, Isnaini; Ramadhan, M. Citra (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This thesis research uses normative legal research, namely research that refers to the legal norms contained in the laws and regulations that apply as a normative footing. Immigration law regulations regarding residence permits for foreign citizens (WNA) in Indonesia during the Covid-19 pandemic: the 1945 Constitution of the Republic of Indonesia, Law of the Republic of Indonesia Number 6 of 2011 concerning Immigration, Government Regulation of the Republic of Indonesia Number 31 of 2013 concerning Guidelines for the Implementation of Law Number 6 of 2011 concerning Immigration. The role of the Immigration Office Special Class I TPI Medan in supervising the residence permit of foreign citizens (WNA) in Medan City during the Covid-19 pandemic: a. The Role of Immigration as a Structural Component, b. The Role of Immigration Oversight of Foreign Citizens (WNA) Stay Permits in Medan City During the Covid-19 Pandemic, c. The Role of Immigration as a Substance Component. d. The Role of Immigration as a Component of Culture or Legal Culture.